Origanum majorana L. Extract Attenuated Benign Prostatic Hyperplasia in Rat Model: Effect on Oxidative Stress, Apoptosis, and Proliferation - Dalia Mahmoud Abdelmonem Elsherbini; Hailah M. Almohaimeed; Mohamed El-Sherbiny; Zuhair M. Mohammedsaleh; Nehal M. Elsherbiny; Sami A. Gabr; Hasnaa Ali Ebrahim (MDPI AG, 2022)
Benign prostatic hyperplasia (BPH) is a widespread androgenic illness influencing elderly men. It is distinguished by prostatic epithelial and stromal muscle cell proliferation. Inflammation, oxidative stress, and apoptosis have all been interrelated to the development of BPH. Marjoram (Origanum majorana L.) is a herb with reported antiproliferative, proapoptotic, and antioxidative properties, which have not yet been studied in relation to BPH. Consequently, in this work, an ethanolic extract of O. majorana was prepared in two doses (250 and 500 mg/kg/day) to be injected into castrated rats after induction of a testosterone-BPH model. Testosterone propionate (TP) was subcutaneously injected (0.5 mg/kg/day) for one week after castration to induce BPH. Forty adult Wistar male rats were randomly allocated into five groups: control, BPH model, high and low O. majorana doses (250, 500 mg/kg/day), and finasteride (FN) (0.8 mg/kg/day) as a positive control. Treatment was continued with drugs/normal saline for 28 days. Rat's body and prostate were weighed, prostate index (PI) and % of prostate growth inhibition were calculated, serum dihydrotestosterone (DHT), prostatic content of superoxide dismutase (SOD), catalase (CAT), total antioxidant capacity (TAC), and malondialdehyde (MDA), DN damage, histopathological changes, immune expression of proliferating cell nuclear antigen (PCNA), caspase-3, α-SMA, and TGF-β1 were assessed. In addition, molecular quantitative PCR and ELISA analyses were performed to identify the expression of mRNAs and related proteins of both caspase-3 and TGF-β1 in prostate tissue from O. majorana-treated and untreated groups. Rats with BPH had significantly higher prostate weights and PI, higher DHT, DNA damage (8-hydroxyguanine, 8-OH-dG), and MDA levels with prominent PCNA, α-SMA, and TGF-β expression, but lower SOD, CAT, and TAC activity and caspase-3 expression. O. majorana (250 and 500 mg/kg/day)-treated groups revealed a decrease in prostate weights and PI, lower levels of DHT, suppressed oxidative stress, reduced tissue proliferation and fibrosis, and restored antioxidant and proapoptotic activity. Additionally, quantitative PCR and ELISA analysis showed that treatment with O. majorana significantly upregulated the expression of caspase-3 and downregulated the expression of TGF-β in prostate tissues of BPH rats. The data were confirmed by the immunohistological reactivity of these targeted markers in the prostate tissues. These effects were more significant with O. majorana 500 mg/mL/rat. In conclusion, the current study indicates the efficient use of O. majorana in the treatment of testosterone-induced BPH through its antiproliferative, proapoptotic, and antioxidative mechanisms.